PENGEMBANGAN DESA WISATA MELALUI RITUAL DESA NOGOSARI KECAMATAN PACET KABUPATEN MOJOKERTO - Mokhammad Ibnu Kawakib (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
This research discusses the cultural diversity and traditions in Indonesia, with a focus on the Kirim Dawuhan tradition in Nogosari Village, Pacet Subdistrict. This tradition is an expression of gratitude by the villagers for the abundant water sources in their village and plays a significant role in environmental preservation and strengthening social bonds within the community. This study aims to address how the development of a Village Tourism through Rituals in Nogosari Village can be achieved and to provide practical and academic contributions to village development and further policies. The research method employed is a qualitative descriptive approach involving four youths from Nogosari Village as informants. The results reveal that the Kirim Dawuhan tradition encompasses the